Spill-over and uncertainty considerations in the active vibration suppression of elastic cantilevered beam - Djojodihardjo, Harijono; Jafari, Mohammad (WSEAS Press, 2015)
Following an efficient analytical method for vibration analysis of an Euler-Bernoulli developed earlier, an extension of this work is carried out for the generic problem of Active Vibration Suppression of a cantilevered Euler-Bernoulli beam with piezoelectric sensor and actuator attached as appropriate along the beam. For comparative study, three generic configurations of the combined beam and piezoelectric elements are illustrated. To assess the robustness of the approach, spill-over effects and uncertainty considerations are elaborated.